Hyperdemocracy - Welch, S. author. aut Link
XIII, 217 p.
Keywords: This book argues that a well-educated citizenry and freer flow of information has contributed to a state of "hyperdemocracy" which impedes itself. This book applies the idea of 'reflexive modernization' to democratic theory, setting out a new perspective on the challenges democracy faces.